The Way to Man's Heart Is through the Stomach - Grossman, Rebecca; Francis, Rohin (The Thoracic and Cardiovascular Surgeon, 2019)
Organ systems do not exist in a vacuum. However, in an era of increasingly specialized medicine, the focus is often on the organ system alone. Many symptoms are associated with differential diagnoses from upper gastrointestinal (GI) and cardiovascular medical and surgical specialties. Furthermore, a large number of rare but deadly conditions cross paths between the upper GI tract and cardiovascular system; a significant proportion of these are iatrogenic injuries from a parallel specialty. These include unusual fistulae, herniae, and embolisms that transcend specialties. This review highlights these conditions and the shared anatomy and embryology of the two organ systems.
Keywords: anatomy; aneurysm; aorta/aortic; cardiac; esophageal surgery